2019
DOI: 10.1111/ele.13253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pesticides on exposure and susceptibility to parasites can be generalised to pesticide class and type in aquatic communities

Abstract: Pesticide pollution can alter parasite transmission, but scientists are unaware if effects of pesticides on parasite exposure and host susceptibility (i.e. infection risk given exposure) can be generalised within a community context. Using replicated temperate pond communities, we evaluate effects of 12 pesticides, nested in four pesticide classes (chloroacetanilides, triazines, carbamates organophosphates) and two pesticide types (herbicides, insecticides) applied at standardised environmental concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 54 publications
0
39
0
Order By: Relevance
“…In the U.S. and Europe, tens of thousands of synthetic chemicals are registered, and in the U.S. >350 pesticides are applied annually 6 , 7 . If the effects of pesticides are consistent within ‘pesticide classes’ (those with similar chemical structures) or ‘pesticide types’ (those targeting similar pests), then the complexity in predicting impacts of pesticides could be markedly reduced 8 , 9 . Such consistency would improve efficiency of risk assessment and allow a greater focus on exceptions to general patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S. and Europe, tens of thousands of synthetic chemicals are registered, and in the U.S. >350 pesticides are applied annually 6 , 7 . If the effects of pesticides are consistent within ‘pesticide classes’ (those with similar chemical structures) or ‘pesticide types’ (those targeting similar pests), then the complexity in predicting impacts of pesticides could be markedly reduced 8 , 9 . Such consistency would improve efficiency of risk assessment and allow a greater focus on exceptions to general patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Further, predicting the effects of pesticides could be simplified if organisms that are taxonomically related or share similar functional roles within an ecosystem have similarities in their responses to pesticides, a trend that has been shown in previous toxicological research (Ippolito et al 2012;Hua & Relyea 2014). For example, our previous research has shown consistency in the effects of pesticides by class and type on parasite transmission, ecosystem functions, and macroinvertebrate and amphibian communities (Rumschlag et al 2019(Rumschlag et al , 2020. In addition, organisms that share functional roles in a community have been shown to respond similarly to types and classes of pesticides (Rumschlag et al 2020).…”
Section: Introductionmentioning
confidence: 85%
“…Respiration was calculated as DO at dusk minus DO at dawn from the following day. Three previous manuscripts, which use the same design as the current manuscript, also describe this experimental design and methods in detail (Rohr et al 2008;Rumschlag et al 2019Rumschlag et al , 2020.…”
Section: Measurement Of Experimental Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S. and Europe, tens of thousands of synthetic chemicals are registered, and in the U.S. >350 pesticides are applied annually ( 3 ). If the effects of pesticides are consistent within ‘pesticide classes’ (those with similar chemical structures) or ‘pesticide types’ (those targeting similar pests), then the complexity in predicting impacts of pesticides could be markedly reduced ( 4 ). Such consistency would improve efficiency of risk assessment and allow a greater focus on exceptions to general patterns.…”
Section: Figurementioning
confidence: 99%